Geant4 simulations of monochromatic Cherenkov radiation in thin quartz targets for different experimental conditions; Journal of Physics: Conference Series; Vol. 2701 : 12th International Conference on Mathematical Modeling in Physical Sciences (IC-MSQUARE 2023) 28/08/2023 - 31/08/2023 Belgrade, Serbia - Dzhurnich B. Blazho; Potylitsyn A. P. Alexander Petrovich; Bogdanov A. V. Aleksey Viktorovich; Gogolev S. Yu. Sergey Yurevich (2024, 2024)
Title screen